ChemInform Abstract: A Versatile Approach to Ullmann C—N Couplings at Room Temperature: New Families of Nucleophiles and Electrophiles for Photoinduced, Copper‐Catalyzed Processes. Issue 8 (25th February 2014) - Ziegler, Daniel T.; Choi, Junwon; Munoz‐Molina, Jose Maria; Bissember, Alex C.; Peters, Jonas C.; Fu, Gregory C.
Abstract This is a new coupling reaction of carbazoles, indoles, benzimidazoles, and imidazoles with various aryl and alkyl halides including hindered, deactivated, heterocyclic aryl iodides, alkenyl and alkynyl halides yielding N‐substituted heterocycles.